2022
DOI: 10.1111/ecc.13624
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and benefits of a videoconferencing‐based home exercise programme for paediatric cancer survivors during the coronavirus disease 2019 pandemic

Abstract: Objective We aimed to determine the feasibility and benefits of a videoconferencing‐based home exercise programme to improve health‐related quality of life (HRQOL), posttraumatic growth and physical strength levels of paediatric cancer survivors during the coronavirus disease 2019 (COVID‐19). Methods Eight paediatric cancer survivors participated in the intervention for 8 weeks. The programme comprised home exercise sessions administered using Zoom, a videoconferencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Twelve studies showed that epidemic home isolation changes lifestyle and physical activity behaviors in adults [11,13,22,23,25,28,29,31,32,36,37,40]. Czyz's study notes an average 34% increase in sedentary time during the epidemic lockdown [28].…”
Section: Large Changes In Physical Activity and Lifestyle Among Adult...mentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve studies showed that epidemic home isolation changes lifestyle and physical activity behaviors in adults [11,13,22,23,25,28,29,31,32,36,37,40]. Czyz's study notes an average 34% increase in sedentary time during the epidemic lockdown [28].…”
Section: Large Changes In Physical Activity and Lifestyle Among Adult...mentioning
confidence: 99%
“…To measure autonomous motivation Kim 2022 [32] online survey An online survey was conducted to empirically develop and test the research model using structural equation modeling (SEM).…”
Section: Author/year Tool Tool Descriptionmentioning
confidence: 99%